2019
DOI: 10.1136/bmjopen-2018-027481
|View full text |Cite
|
Sign up to set email alerts
|

Associations between socioeconomic position and changes in children’s screen-viewing between ages 6 and 9: a longitudinal study

Abstract: ObjectivesTo explore socioeconomic differences in screen-viewing at ages 6 and 9, and how these are related to different media uses.DesignLongitudinal cohort study.SettingChildren recruited from 57 state-funded primary schools in Southwest England, UK.Participants1299 children at ages 5–6, 1223 children at ages 8–9, including 685 children at both time points.Outcome measuresChildren’s total screen-viewing time (parent-reported) and time spent using multiple screen devices simultaneously (multiscreen viewing), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Similar findings were found in another study by the same authors examining outdoor advertising in the UK—little difference in the nutritional content of advertised foods was observed between the most and least affluent areas, but the total advertising space was greatest in the least affluent areas 19 . For television advertising, the higher absolute exposure to unhealthy food advertising aligns with the relatively consistent findings in the literature that ethnic minority children or children from families with a lower SEP spend a greater amount of time watching television 39–42 . For outdoor advertising, a greater total exposure of advertising in lower SEP and ethnic minority neighbourhoods may reflect targeted advertising by corporations, cheaper advertising rates 43 or a higher density of stores and fast food outlets 44,45 .…”
Section: Discussionsupporting
confidence: 86%
“…Similar findings were found in another study by the same authors examining outdoor advertising in the UK—little difference in the nutritional content of advertised foods was observed between the most and least affluent areas, but the total advertising space was greatest in the least affluent areas 19 . For television advertising, the higher absolute exposure to unhealthy food advertising aligns with the relatively consistent findings in the literature that ethnic minority children or children from families with a lower SEP spend a greater amount of time watching television 39–42 . For outdoor advertising, a greater total exposure of advertising in lower SEP and ethnic minority neighbourhoods may reflect targeted advertising by corporations, cheaper advertising rates 43 or a higher density of stores and fast food outlets 44,45 .…”
Section: Discussionsupporting
confidence: 86%
“…Several studies, with both cross-sectional [ 16 , 17 , 18 , 19 ] and longitudinal [ 23 , 24 , 25 ] designs, have shown an inverse association between parental educational level and the time spent in front of a screen in children. These findings are aligned with the results of the present study which additionally showed that a lower maternal educational level was predictive for not meeting screen-time recommendation for children.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that maternal educational level, measured as a proxy of the child’s socioeconomic status, is related to the child’s diet quality, physical activity, and screen time [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Cross-sectional data indicates that children whose mothers have a low educational level are at higher risk of reporting an unhealthy diet, a low level of physical activity, and high level of screen time [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, socioeconomic status, such as education, income and deprivation, is associated with children's media viewing and health status. Many studies have found an increase in media viewing time and sedentary time as the socioeconomic status decreases [72][73][74][75][76][77][78]. An increase in sedentary time can lead to a decrease in the time spent engaging in play and sports activities, which in turn can reduce manual dexterity.…”
Section: Discussionmentioning
confidence: 99%